2005
DOI: 10.1080/01448765.2005.9755320
|View full text |Cite
|
Sign up to set email alerts
|

Manure Nitrogen Availability: Dairy Manure in Northeast and Central U.S. Soils

Abstract: Accurate prediction of nitrogen (N) availability from manure is required for efficient utilization of this resource in crop production. This study was conducted to evaluate the impacts of temperature, water regime and selected soils on N availability from a liquid dairy (Bas taurus) manure. Two Maine soils [Caribou sandy loam (fine-loamy, mixed, frigid Typic Haplorthod) and 'Newport' loam (unnamed variant of a Bangor silt loam; coarse-loamy, mixed, frigid Typic Haplorthod)] and an Illinois soil [Catlin silt lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
2
11
3
Order By: Relevance
“…The amount of ammonium produced was not significantly higher in the soil containing manure compared to that of unamended soils. This result differs from that reported by Honeycutt, Griffin, and He (2005), who used dairy manure in their study, and is probably because dairy compost was used in this study and the NH 4 had already undergone nitrification (NH 4 conversion to NO 3 ) or had been volatilized. In the succeeding text, the amount of inorganic N is expressed as the sum of NH 4 and NO 3 .…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…The amount of ammonium produced was not significantly higher in the soil containing manure compared to that of unamended soils. This result differs from that reported by Honeycutt, Griffin, and He (2005), who used dairy manure in their study, and is probably because dairy compost was used in this study and the NH 4 had already undergone nitrification (NH 4 conversion to NO 3 ) or had been volatilized. In the succeeding text, the amount of inorganic N is expressed as the sum of NH 4 and NO 3 .…”
Section: Resultscontrasting
confidence: 56%
“…Unlike results reported by Honeycutt, Griffin, and He (2005), who performed a similar experiment, we did not observe N immobilization in the Catlin soil. They reported that soil with higher clay and silt contents showed greater N immobilization when amended with dairy manure compared to the other soils.…”
Section: N Mineralization Affected By Wet/dry Cyclescontrasting
confidence: 56%
“…The same soil was studied since mineralization varies among soils (Honeycutt et al 2005 (Richard 2005) and that 400 g N (kg total N) -1 would be mineralized from manure (Eghball and Power 1999). We used these assumed values to determine each year's application rates of solid manure (never a slurry) and compost.…”
Section: Site Soils and Amendmentsmentioning
confidence: 99%
“…Many laboratory studies have evaluated mineralization rates at optimal soil water contents and temperatures for diff erent soils or manures (Chae and Tabatabai, 1986;Qian and Schoenau, 2002;Van Kessel and Reeves, 2002;Griffi n et al, 2005;Honeycutt et al, 2005;Azeez and Van Averbeke, 2010;Miller et al, 2010). Unfortunately, N mineralization rates derived from laboratory incubations generally overestimate rates measured in the fi eld (Adams and Attiwill, 1986;Honeycutt, 1999;Sistani et al, 2008).…”
mentioning
confidence: 99%